Италмас: легенда на русском и удмуртском языках / Михаил Петров ; [перевод с удмуртского В. Семакина ; художник Э. Морозов] - Петров Михаил Петрович (Удмуртия, 1984)
Экземпляры: КР (20000908) / Инвентарный номер: у32912 / Сис.шифр: С(Удм) / Авт.знак: П 30 / ГРНТИ: 17.82 / ББК: 84(2)